Variasi Jenis Lengkungan Kaki pada Atlet dari Berbagai Cabang Olahraga: Analisis dan Implikasinya terhadap Performa Atletik - Resmana, Dadan; Ganeswara, Raisa; Sutiyono, Bambang; Yuliana, Ela; Oktafiranda, Nadya; Wattimena, Ferry Yohannes (Institut Teknologi Bandung, 2024)
The foot arch is one of the many parts of the leg that plays a crucial role in supporting and balancing body weight, as well as regulating body movement during walking and running. Despite this, research on the foot, particularly in student-athletes, remains limited. Therefore, this study aims to analyze the variations in arch types of the foot among student-athletes from various sports disciplines. The research employs an observational study method with participants being student-athletes from soccer, futsal, archery, and pencak silat. Foot measurements are taken using the wet test, while height is measured with a stadiometer, and body weight and BMI are assessed using the Omron Carada Body Fat Scan. The results indicate that futsal and soccer athletes predominantly have normal foot arches, with 90% in each group, while only 10% exhibit flat arches. In contrast, archery and pencak silat athletes show a greater variation in arch distribution, with 30% and 40% having flat arches, and 70% and 60% having normal arches, respectively. The study concludes that while normal foot arches are the most common among athletes, the distribution of foot arches varies by sport, which may reflect the biomechanical needs and specific training patterns inherent to each sport.